2017
DOI: 10.1002/jgm.2971
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to HIV‐1 infection is influenced by toll like receptor‐2 (−196 to −174) polymorphism in a north Indian population

Abstract: The present study reports for the first time that the TLR2-196 to -174 Ins/Del polymorphism is a risk factor for HIV-1 transmission in HIV-1 infected North Indian individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…TLR2 Del homozygous genotype may be associated with reduced risk of HIV-1 disease progression. [ 51 ] The results of TLR2 (rs5743708, rs5743704) were same as Soriano-Sarabia et al results. [ 43 ] The remaining results of the Vidyant study pointed out TLR4 rs4986790 is associated with stage progression, but not observed in TLR4 rs4986791.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…TLR2 Del homozygous genotype may be associated with reduced risk of HIV-1 disease progression. [ 51 ] The results of TLR2 (rs5743708, rs5743704) were same as Soriano-Sarabia et al results. [ 43 ] The remaining results of the Vidyant study pointed out TLR4 rs4986790 is associated with stage progression, but not observed in TLR4 rs4986791.…”
Section: Resultssupporting
confidence: 80%
“…The study performed on an Indian cohort indicated that TLR2 –196 to –174 Ins/Del polymorphism is a risk factor for HIV-1 infection. [ 51 ] Compared with healthy controls, TLR2 Del mutant genotype (OR = 2.138; P = .001) and allele (OR = 1.562; P = .002) was higher in patients with HIV-1 infection. This correlation did not find in other TLR2 genes (rs5743708, rs5743704, rs12191786).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of malaria contributing to positive selection and emergence of 'ins' allele of TLR2 gene in higher primates, the observation that humans with 'del' allele are prone to increased TLR2 mediated inflammation has opened up avenues for future investigations on innate immunity/ inflammation in humans. Both innate as well as adaptive immune responses are directly influenced by TLR-2 mediated activation of dendritic cells and T lymphocytes [32][33][34] and thus 'ins' vs 'del' in TLR2 gene could influence host response and susceptibility of humans to several other diseases such as HIV-AIDS 35 , H. pylori mediated gastric cancer 36 and Alzheimer's disease 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Infection of TLR2 knockout mice with Friend virus (FV), a gammaretrovirus, revealed no impact on viral loads or immunity (E Browne unpublished observation), but genetic evidence from humans has indicated a possible role for TLR2 in HIV infection and disease progression. Specifically, a deletion allele of TLR2 (−196 to −174 Ins/Del) is associated with elevated risk of HIV infection and faster disease progression [51,52]. The mechanism behind how this genetic variant impacts HIV infection is still unclear.…”
Section: Tlr2mentioning
confidence: 99%